The role of environmental factors in regulating the development of cartilaginous grafts engineered using osteoarthritic human infrapatellar fat pad-derived stem cells. - KELLY, DANIEL JOHN; BUCKLEY, CONOR TIMOTHY (My University, 2012)
Engineering functional cartilaginous grafts using stem cells isolated from osteoarthritic human tissue is of fundamental importance if autologous tissue engineering strategies are to be used in the treatment of diseased articular cartilage. It has previously been demonstrated that human infrapatellar fat pad (IFP)-derived stem cells undergo chondrogenesis in pellet culture; however, the ability of such cells to generate functional cartilaginous grafts has not been adequately addressed. The objective of this study was to explore how environmental conditions regulate the functional development of cartilaginous constructs engineered using diseased human IFP-derived stem cells (FPSCs). FPSCs were observed to display a diminished chondrogenic potential upon encapsulation in a three-dimensional hydrogel compared with pellet culture, synthesizing significantly lower levels of glycosaminoglycan and collagen on a per cell basis. To engineer more functional cartilaginous grafts, we next explored whether additional biochemical and biophysical stimulations would enhance chondrogenesis within the hydrogels. Serum stimulation was observed to partially recover the diminished chondrogenic potential within hydrogel culture. Over 42 days, stem cells that had first been expanded in a low-oxygen environment proliferated extensively on the outer surface of the hydrogel in response to serum stimulation, assembling a dense type II collagen-positive cartilaginous tissue resembling that formed in pellet culture. The application of hydrostatic pressure did not further enhance extracellular matrix synthesis within the hydrogels, but did appear to alter the spatial accumulation of extracellular matrix leading to the formation of a more compact tissue with superior mechanically functionality. Further work is required in order to recapitulate the environmental conditions present during pellet culture within scaffolds or hydrogels in order to engineer more functional cartilaginous grafts using human osteoarthritic FPSCs.
PUBLISHED
Keywords: human osteoarthritic FPSCs; human osteoarthritic FPSCs